RAGAM BENTUK TINGGALAN BUDAYA MEGALITIK Dl PAPUA (Variation of Megalithic Culture in Papua) - Djami, Erlin Novita ldje (BALAI ARKEOLOGI PAPUA, 2016)
Papua is a place which is potential to have variety of cultural heritage of megalithic, and it spreads over the Papua. The megalithic tradition has been in this area since the prehistory period, even this it is continuing until today. The influence of this culture in Papua came from the west side through Sulawesi, Maluku and finally reached to Papua. Moreover, from the north side, it came through the Mikronesia area, Melanesia dan then arrived to Papua. The culture of megalithic is believed that it is influnced by the Austronesia people. The forms of megalithic in Papua include the terraces stone, mareuw, stone pole, ainining duka, mortar stone, sharpening stone, stone path, soul path, stone enclosure, megalithic archa, woming stone, throne stone, menhir (standing stone), table stone (dolmen), engraving stone, carving stone, totor, and turtle stone. This discovery of megalithic culture is related with the religious activity dan the other social cuture activities. AbstrakPapua merupakan salah satu wilayah yang memiliki potensi keberadaan tinggalan budaya megalitik yang cukup banyak dan beragam bentuknya, lokasinya tersebar hampir di seluruh wilayah tersebut. Kehadiran tradisi megalitik di wilayah ini, sudah ada sejak zaman prasejarah, bahkan di beberapa tempat di Papua tradisi megalitik masih berlangsung hingga kini. Pengaruh budaya megalitik di wilayah Papua datang melalui dua jalur yaitu jalur barat melalui daerah Sulawesi, Maluku, hingga sampai ke Papua. Sedangkan jalur utara melalui wilayah Mikronesia, Melanesia, dan sampai ke Papua. Keberadaan budaya megalitik di Papua sebagai salah satu bentuk pengaruh dari bangsa Austronesia. Bentuk-bentuk tinggalan megalitik di wilayah Papua berupa bangunan berundak, mareuw, tiang batu, ainining duka, lumpang batu, batu asah, jajaran batu, jalan arwah, batu temugelang, area megalitik, batu peringatan, tahta batu, menhir, dolmen, batu bergores, pahatan batu, totor, dan batu teteruga. Temuantemuan tinggalan budaya tradisi megalitik tersebut berkaitan erat dengan aktivitas religi dan aktivitas sosial budaya lainnya.